3D CT Angiography of Infrarenal Abdominal Aortic Aneurysm with Associated Ectopic Pelvic Kidney: A Case Report of Rare Concomitance - Shen, Y.; Sun, Zhonghua; Xu, L.; Li, Y.; Zhang, N.; Fan, Z. (Bentham Science Publishers, 2015)
The abdominal aortic aneurysm (AAA) associated with congenital pelvic kidney is a rare clinical finding. We present a case of an infrarenal AAA with associated congenital left pelvic kidney followed up for 5 years, which was managed by regular surveillance. We describe this case to assist physicians and radiologists to recognize small aneurysmsby computed tomography angiography (CTA) with low radiation dose and low iodine dose. To the best of our knowledge,this case is the first report by using CTA with the combination of low-concentration contrast medium, low radiation doseand iterative reconstruction.